(untitled) (Research, Society and Development, 2022)
Since, since ancient times, gastronomy is highly influenced by society and also changes and influences the way of life and eating habits of the same. In this context, this article aims to address how some religions change the way people see certain foods. This view ranges from prohibitions and restrictions to the importance of certain foods in some religions, as part of the culture. This research is characterized as an integrative literature review, where selected articles were analyzed through the inclusion criteria. It is based on the theme “Religion and food consumption: Review”. Literature published in English and Portuguese was sought as a priority for the study. For this, a literature search was carried out using some keywords such as: Gastronomy; Food; Religion. This article intends to develop a reflection on how religion influences the consumption of certain foods around the world and how it affects people’s lives. Some customs and eating habits of some religions such as Catholicism, Buddhism and Hinduism will also be addressed. This article is based only on bibliographic analyzes and analyzes of materials produced by other specialists.